The Impact of the COVID-19 Pandemic on Staff in Violence Against Women Services - Burd, Caitlin (Violence against women, 2023)
The COVID-19 pandemic has been harmful to survivors of abuse. Less understood is the impact on staff in the violence against women (VAW) service sector. Using interpretive description methodology, we examined staff experiences during the pandemic in Ontario, Canada, and found four core themes: (1) the emotional toll of the work; (2) remote (doesn't) work; (3) work restructuring; (4) efforts to stay well and subthemes nuancing staff experiences in a sector vulnerable to vicarious trauma. This research underscores the need to mitigate experiences of stress, heavy workloads, and guilt for staff in VAW services during crises and provides action-oriented recommendations.